2012
DOI: 10.1111/j.1744-7909.2012.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Architecture of Flowering Time and Photoperiod Sensitivity in Maize as Revealed by QTL Review and Meta Analysis

Abstract: The control of flowering is not only important for reproduction, but also plays a key role in the processes of domestication and adaptation. To reveal the genetic architecture for flowering time and photoperiod sensitivity, a comprehensive evaluation of the relevant literature was performed and followed by meta analysis. A total of 25 synthetic consensus quantitative trait loci (QTL) and four hot-spot genomic regions were identified for photoperiod sensitivity including 11 genes related to photoperiod response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 111 publications
2
57
0
Order By: Relevance
“…However, the high sensitivity of tropical maize germplasms to photoperiods limits its planting distribution and production [5, 7]. Photoperiod-sensitive maize lines/hybrids with tropical germplasm are characterized in part by delayed flowering and/or failure of seed setting under long photoperiods (LP) [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, the high sensitivity of tropical maize germplasms to photoperiods limits its planting distribution and production [5, 7]. Photoperiod-sensitive maize lines/hybrids with tropical germplasm are characterized in part by delayed flowering and/or failure of seed setting under long photoperiods (LP) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Maize genes and noncoding regions involved in the timing of the vegetative-to-floral transition include Vegetative to generative transition1, Zea CENTRORAPIALIS8, and indeterminate1 (Salvi et al, 2007;Lazakis et al, 2011). Substantial natural phenotypic variation has been reported for these traits in maize (Chardon et al, 2004;Salvi et al, 2007;Buckler et al, 2009;Chen et al, 2012;Xu et al, 2012). However, to date, the genetic architecture of these important developmental transitions has not been explored in the context of a species pan-genome.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of the maize ZmDof1 gene in rice promoted N assimilation under low-N conditions (Kurai et al 2011) and NUE is apparently improved because of the overexpression of the GS gene (a member of the GS1 gene family) in maize transgenic lines (Fu et al 2013;Martin et al 2006). Currently many data on low-N tolerance QTLs and large-scale gene expression at the genomic-wide level have already been released (Xu et al 2012b;Eveland et al 2010), along with the functionally identified low-N-related genes, which comes a great opportunity to further dissect this complex trait by integrating these information. In this study, we employed meta-analysis to obtain specific low-N-induced cQTLs in the first place, excluding the cQTL detected under both low-N and other environmental conditions in maize.…”
Section: Discussionmentioning
confidence: 97%